Dealing With Omitted and Not-Reached Items in Competence Tests: Evaluating Approaches Accounting for Missing Responses in Item Response Theory Models. (June 2014) - Pohl, Steffi; Gräfe, Linda; Rose, Norman
Data from competence tests usually show a number of missing responses on test items due to both omitted and not-reached items. Different approaches for dealing with missing responses exist, and there are no clear guidelines on which of those to use. While classical approaches rely on an ignorable missing data mechanism, the most recently developed model-based approaches account for nonignorable missing responses. Model-based approaches include the missing propensity in the measurement model. Although these models are very promising, the assumptions made in these models have not yet been tested for plausibility in empirical data. Furthermore, studies investigating the performance of different approaches have only focused on one kind of missing response at once. In this study, we investigated the performance of classical and model-based approaches in empirical data, accounting for different kinds of missing responses simultaneously. We confirmed the existence of a unidimensional tendency to omit items. Indicating nonignorability of the missing mechanism, missing tendency due to both omitted and not-reached items correlated with ability. However, results on parameter estimation showed that ignoring missing responses was sufficient to account for missing responses, and that the missing propensity was not needed in the model. The results from the empirical study were corroborated in a complete case simulation.